Type of Risk in Halal Food Supply Chain: A Review - Fadhlur Rahim Azmi; Abu Abdullah; Eko Ruddy Cahyadi; Haslinda Musa; Juan Rizal Sa’ari (International Journal of Supply Chain Management, 2020)
The main purposes of this paper are to identify the risks involved in the halal food supply chain in an article published in the context of halal management. The study utilized an extensive literature review to identify the type of risks in published articles. The study has found nine significant risks in the halal food supply chain which is human resource, processing risk, logistic risk, raw material risk, halal certification, traceability, market characteristic, outsourcing practices and product characteristic. This review includes many present studies and is a source of beneficial references for examining risk in the halal food supply chain.